The amalgamation of digital and leadership as a key role in organization: Literature review - Wijaya, Andreas; Hamidah; Fauzi, Achmad (IJHCM (International Journal of Human Capital Management), 2024)
Digital leadership became prominent to bridging Digital transformation in organizations. Despite, a lot of research in digital leadership topic has soared, it still misses the gap for the position of digital leadership. This research investigates the determination of digital leadership based on literature review from various research articles and presents the position of digital leadership. Therefore, this study was conducted with the Grounded Theory Literature-Review Method and perish n publish or perish to collect proper literature, data was presented using the matrix augmented of unit analysis, and the data was categorized by variable, theory, and unit analysis. The results showed three positions of digital leadership, firstly ten articles positioned digital leadership as independent variable.  Secondly, one study conducted digital leadership as  mediating variable, and lastly,  there were two research studied digital leadership as moderating variable. This study concludes the theme of digital leadership was frequently used to develop digital transformation and performance for organizations. Leaders act as a supporter and connectors between corporate culture and team members to bridge the transformation. Furthermore, it remains a gap in digital leadership variable research topics such as: measuring dimensions of digital leadership, competence of the leader, and which leadership styles suitable for organizations.